Students' Perception of Task-Based Learning in EFL Teaching Methods and its Impact on English Writing Skills - Nunenk Lanang Teguh Mahmud; Usuluddin Usuluddin; Hajriana Arfah; Ari Prasetyaningrum (Departement of Mathematics Education, 2024)
Many students in EFL contexts face challenges in developing writing skills, highlighting the need for effective instructional approaches. This study aims to evaluate the effectiveness of the EFL learning approach in enhancing the writing abilities of seventh-grade students. To address this, the research assessed the impact of the EFL approach using a pre-experimental design with a one-group pre-test and post-test model. Conducted with 25 seventh-grade students from SMPN 1 SAKRA BARAT, the study involved measuring writing skills before and after the Task-Based learning intervention. The study revealed that students’ writing skill in such element like grammar, vocabulary, and content structured comprehension were increased, 5% of the students gained “good” category in grammar, 9% advanced into “good” in vocabulary, and 11% of the students in understanding content achieved “good” category as well. These findings indicate that the EFL learning approach effectively improves students' writing abilities. The study provides valuable insights into the benefits of the EFL approach, suggesting its practical effectiveness in enhancing writing instruction and offering implications for educators and curriculum developers.